Country of Origin Image and Brand Equity from Gender Perspective: Do they matter? - Septyanti, Astrid Vega; Hananto, Arga (Department of Management, Faculty of Economics and Business, Brawijaya University, 2017)
This study investigated how country of origin image and brand equity dimensions affect overall brand equity. In addition, this study also investigated whether there is gender difference in the hypothesized relationship. A partial least square structural equation modeling with multigroup analysis was carried out on a sample of 171 respondents selected using purposive/convenience sampling technique. The result indicates that country of origin have indirect effect toward brand equity through two dimensions of brand equity (perceived quality and brand loyalty). This study also found that country of origin imageâ€™s association with brand awareness/association is stronger for female shoppers than for male shoppers.Â This study adds more insights about how male and female consumers reacto country of origin image